2014
DOI: 10.1038/onc.2014.377
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Mdm2SNP309-G allele on a murine model of colorectal cancer

Abstract: A single-nucleotide polymorphism (SNP) in the promoter of the Mdm2 gene (Mdm2(SNP309-G)) results in an increased Mdm2 expression, partial attenuation of the p53 pathway and accelerated tumor development. Clinical case-control studies indicate the Mdm2(SNP309-)(G) allele associates with a significant increase in colorectal cancer (CRC) risk that is heightened in women, but the biological significance of this polymorphism has never been directly evaluated. To examine whether the Mdm2(SNP309-)(G) allele contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The results from all four meta‐analyses came to a same conclusion: the variant G allele of the polymorphism was associated with an increased colorectal cancer risk among Asians but not Caucasians. The risk increment was consistent with the observation that the G allele has an enhanced affinity towards the Sp1 transcription factor, which results in an increased MDM2 transcription and eventually a higher protein level . This effectively attenuates the tumor suppressor functions of p53, leading to a heightened risk of cancer.…”
Section: Genes Encoding Transcription Factors and Related Proteinssupporting
confidence: 86%
See 1 more Smart Citation
“…The results from all four meta‐analyses came to a same conclusion: the variant G allele of the polymorphism was associated with an increased colorectal cancer risk among Asians but not Caucasians. The risk increment was consistent with the observation that the G allele has an enhanced affinity towards the Sp1 transcription factor, which results in an increased MDM2 transcription and eventually a higher protein level . This effectively attenuates the tumor suppressor functions of p53, leading to a heightened risk of cancer.…”
Section: Genes Encoding Transcription Factors and Related Proteinssupporting
confidence: 86%
“…The risk increment was consistent with the observation that the G allele has an enhanced affinity towards the Sp1 transcription factor, which results in an increased MDM2 transcription and eventually a higher protein level. 141 This effectively attenuates the tumor suppressor functions of p53, leading to a heightened risk of cancer. The MDM2 c.14+309 T>G polymorphism can therefore serve as a potential biomarker for predicting predisposition to colorectal cancer among Asians.…”
Section: Mdm2mentioning
confidence: 99%
“… 19 In vivo mouse models clearly demonstrated that the inactivation or loss of p53 stimulates tumorigenesis, whereas established tumors are disappeared or diminished after restoration of p53. 60 These data indicate that recovery of wild-type p53 function is a valid therapeutic approach, and the specific targeting of MDM2/MDMX to reactivate p53 is a viable anticancer strategy. 61 On the basis of this notion, structure-based drug design has led to the discovery of several MDM2 or MDMX antagonists that block the interactions between murine double minute (MDM) and p53, leading to p53 stabilization and activation for cancer treatment.…”
Section: Mechanisms Of Ring-type E3 Ligases In Crcmentioning
confidence: 93%
“…MDM2 SNP309 has been shown to modify this cancer risk in multiple cohorts of TP53 mutation carriers in an ageand gender-dependent manner. [22][23][24][25][26] Importantly, genetically engineered mouse models carrying either alleles of MDM2 SNP309 and a highly penetrant LFS p53 mutation demonstrated similar allele-specific differences in age-dependent cancer incidence. 26 Together, observations such as these suggest that SNPs could potentially modify ACC cancer risk.…”
Section: Introductionmentioning
confidence: 97%
“…[22][23][24][25][26] Importantly, genetically engineered mouse models carrying either alleles of MDM2 SNP309 and a highly penetrant LFS p53 mutation demonstrated similar allele-specific differences in age-dependent cancer incidence. 26 Together, observations such as these suggest that SNPs could potentially modify ACC cancer risk. Here, we studied two independent cohorts of ACC patients (paediatric and adult) to demonstrate that a SNP in a druggable gene and pathway significantly associates with ACC age-dependent incidence.…”
Section: Introductionmentioning
confidence: 97%